2020
DOI: 10.1007/s00228-020-02903-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity in patients with solid tumors treated with PD-1/PD-L1 inhibitors alone, PD-1/PD-L1 inhibitors plus chemotherapy, or chemotherapy alone: systematic review and meta-analysis

Abstract: Background This meta-analysis examined the risk of hepatotoxicity in patients with solid tumors who received a PD-1/PD-L1 inhibitor alone, a PD-1/PD-L1 inhibitor plus chemotherapy, or chemotherapy alone. Methods Potentially eligible studies were identified by searches of Embase and PubMed. All included studies were randomized controlled trials (RCTs) that examined patients with solid tumors who received a PD-1/PD-L1 inhibitor and/or chemotherapy. Results We included 20 clinical trials (11,634 patients). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
4
5
0
Order By: Relevance
“…These findings match with the previous studies reporting mild elevation of liver transaminases induced by CP standard doses [ 36 ], yet, this does not usually coincide with hepatic histopathological changes, as aforementioned [ 35 ]. Indeed, treatment with CP showed mild central necrotic areas in liver sections that could be probably caused by CP hepatic metabolism [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings match with the previous studies reporting mild elevation of liver transaminases induced by CP standard doses [ 36 ], yet, this does not usually coincide with hepatic histopathological changes, as aforementioned [ 35 ]. Indeed, treatment with CP showed mild central necrotic areas in liver sections that could be probably caused by CP hepatic metabolism [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, immune-mediated hepatitis has been reported in patients with solid tumors receiving immunotherapy, while lacking signs of blood hepatotoxicity. This explains our findings of inflammatory hepatic reaction with all adopted treatments that was associated with improvement of hepatic transaminases [ 35 ].…”
Section: Discussionsupporting
confidence: 52%
“…Tese alterations in biochemical parameters strongly correlate with several deleterious renal histological changes and lesions, including degenerative changes and nuclear pyknosis of the lining epithelium of the renal tubules, associated with glomerulonephritis, focal interstitial nephritis, and congestion. Other studies have shown similar histological alterations [55,[61][62][63]. Paclitaxel-induced nephrotoxicity may refect the alteration and degeneration of glomerular composition and decreased glomerular fltration rate in rats [60].…”
Section: Discussionmentioning
confidence: 78%
“…Immune checkpoint inhibitors (ICIs) have been a cornerstone of treatment in a variety of previously difficult-to-treat cancers but are associated with a variety of immune-mediated adverse effects, including hepatotoxicity [97]. Guo et al performed a large literature review of clinical trials that evaluated PD-1/PD-L1 compared to traditional chemotherapy and found that PD-1/PD-L1 treatment was associated with increased risk of all-grade hepatitis (RR = 5.85, p < 0.01), and high-grade hepatitis (RR = 5.66, p < 0.01) [98]. Various groups have reported the incidence and clinical signature of immune-mediated liver injury (ILICI) in the past year [99][100][101][102][103][104][105].…”
Section: Icismentioning
confidence: 99%